Contemporary Summer Village Assemblies in Central Serbia and (Generational) Performative Practices of Older and Newer Rural Vocal Layers - Jovanović, Jelena (Interdisciplinary Studies in Musicology, 2022)
For the present day middle-aged and older village singers in the Šumadija region in central Serbia rural singing festivals are quite popular events: these are occasions for local communities to share their enthusiasm and to communicate through songs, sharing the elements of tradition they all consider theirs, inventing new lyrics to well-known traditional melodies (’standards’), socializing, and confirming their friendships based on pure satisfaction in common singing. On such occasions there appears an opposition in relation to Serbian old and new traditional vocal rural layers (see more for ex. Petrović and Jovanović, 2003, Golemović, 2016). Namely, for village middle-aged and older singers, the main common means of expression are recent or newer rural singing with structural elements closer to the European ones. Old-time rural singing, with its second chords in two-part texture, non-tempered scales, more hermetic in character, shows differences between regional local traditions, and hence has not been regarded as a common way of musical communication for village singers. On the other hand, younger neotraditional singers, in professional or amateur ensembles mostly from towns and mostly conducted by ethnomusicologists, have been devotees of old-time singing as a strong endemic musical device, rich in musical, ethical, and expressive sense. At the festivals they sing such songs to awaken and demonstrate their value in the settings where they are already lost from living practice. This paper is based on the principles of applied ethnomusicology, on long-term fieldwork and on scholarly researches in Šumadija, as well as on personal performing and teaching experiences.